Arctic observations and numerical simulations of surface wind effects on Multi-Angle Snowflake Camera measurements - K. E. Fitch; C. Hang; A. Talaei; T. J. Garrett (Atmospheric Measurement Techniques, 2021)
Ground-based measurements of frozen precipitation are heavily influenced by interactions of surface winds with gauge-shield geometry. The Multi-Angle Snowflake Camera (MASC), which photographs hydrometeors in free-fall from three different angles while simultaneously measuring their fall speed, has been used in the field at multiple midlatitude and polar locations both with and without wind shielding. Here, we present an analysis of Arctic field observations – with and without a Belfort double Alter shield – and compare the results to computational fluid dynamics (CFD) simulations of the airflow and corresponding particle trajectories around the unshielded MASC. MASC-measured fall speeds compare well with Ka-band Atmospheric Radiation Measurement (ARM) Zenith Radar (KAZR) mean Doppler velocities only when winds are light ( ≤5<mspace linebreak="nobreak" width="0.125em"/>m<mspace linebreak="nobreak" width="0.125em"/>s-1 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c22dcb727417217cf78bb9552cac1fa5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-14-1127-2021-ie00001.svg" width="46pt" height="14pt" src="amt-14-1127-2021-ie00001.png"/></svg:svg> ) and the MASC is shielded. MASC-measured fall speeds that do not match KAZR-measured velocities tend to fall below a threshold value that increases approximately linearly with wind speed but is generally <math xmlns="http://www.w3.org/1998/Math/MathML" id="M2" display="inline" overflow="scroll" ...